Words, films and modernities : a socio-political and semio-narratological approach of modernity in cinema : durassian cinema of vacuous and french speaking african cinema - (:unkn) unknown (My University, 1998)
Modernity in cinema in the sixties and the seventies, defined as a political speech in cinema on national and world scale, has been reduced to the only crisis of foundations. Such a conception neglects research of foundations in this cinematographically modernity specially met in the third world, and gives substance to the actual thesis of "return of the fiction". In this work, we favor diversity and decentration, in order to show the impossibility to decree the end of this cinematographically modern movement, thus its stakes and consequences have been at the same time explicit and subtle, similar and opposed, international and fundamentally local. we adopt a decentration of interpretation, studying this modernity not only as crisis of foundations, but also as research of these foundations ; a decentration of method, that is not only socio-political but also semio-narrative; finally a decentration of films corpus, analyzing in a chiasmatical approach, two "modern" cinemas radically different: the movies of M. Duras defined by the crisis of certitudes, the vacuous, and the French-speaking African cinema researching the fullness of authentic African cultural identity. Words as action ("la parole-action") and as narration ("la parole-recit") have a great place in these two "modern" cinemas. We study them in relation with the socio-political reality (1rst part),with the otherness and the utopia (2nd part), with the problem of reception (3rd part),with the question of narration (4th part), with the concept of movement as a great concept around the notion of modernity (5th part). Beyond films socio-political and semio- narrative analysis, this work is also a reflexing about anthropology of modernity in cinema.
Keywords: African Research